Material-Driven Therapeutics: Functional Nanomaterial Design Paradigms Revolutionizing Osteosarcoma Treatment - Zewei Zhang; Fang He; Wenqu Li; Beibei Liu; Cheng Deng; Xiaojuan Qin (Journal of Functional Biomaterials)
Osteosarcoma (OS), a prevalent primary malignant bone tumor in children and adolescents, has maintained consistent treatment protocols since the 1970s combining surgery, chemotherapy, and radiotherapy. While effective for localized tumors, these strategies show limited efficacy against metastatic or recurrent cases. Although emerging immunotherapies (PD-1 inhibitors, CAR-T-cell therapy) demonstrate therapeutic potential, their clinical impact remains constrained by the tumor’s low immunogenicity and immunosuppressive microenvironment, resulting in suboptimal response rates. The disease’s aggressive nature and propensity for pulmonary metastasis contribute to poor prognosis, with survival rates showing negligible improvement over five decades despite therapeutic advances, creating substantial clinical and socioeconomic challenges. Recent developments in nanomedicine offer promising solutions for OS treatment optimization. This review systematically examines nanomaterial applications in OS therapy through a materials science lens, analyzing mechanism-specific interventions and highlighting notable advancements from the past five years. We critically evaluate current strategies for enhancing therapeutic efficacy while reducing toxicity profiles, ultimately outlining translational pathways and key challenges in clinical adaptation. The analysis establishes a framework for developing next-generation nanotherapeutic platforms to address persistent limitations in OS management.